Release of a Soluble Phytoalexin Elicitor from Mycelial Walls of Phytophthora megasperma var. sojae by Soybean Tissues - Yoshikawa, Masaaki (1981)
A soluble elicitor of glyceollin accumulation was released from insoluble mycelial walls of Phytophthora megasperma var. sojae after incubation with soybean cotyledon tissue for as little as 2 minutes. Various enzymic and chemical treatments of the released elicitor indicated that the activity resided in a carbohydrate moiety, and gel filtration disclosed the presence of at least two active molecular species. Cell-free extracts from soybean cotyledons or hypocotyls also released soluble elicitors from fungal cell walls that were similar to those released by living cotyledon tissue. These results may suggest that contact of fungal pathogens with host tissues is required to release fungal wall elicitors which then initiate phytoalexin accumulation in the plant.